Treehoppers (Hemiptera: Aetalionidae and Membracidae) from Madre de Dios region, Peru - Lin, Chung-Ping (2019)
A list of treehoppers (Aetalionidae and Membracidae) is presented from Madre de Dios region at the southeastern Amazon basin in Peru. The treehopper specimens were collected as by-catch in a survey of the beetles in the Villa Carmen Biological Station and Los Amigos Biological Station. The list comprises 44 species, 31 genera, 16 tribes and 9 subfamilies. Ten genera are new records to Peru. The images of representative specimens of each identified species and genera are provided to facilitate the identification of the local treehopper fauna.